South African Broadcasting Corporation's editorial coverage of community protests towards the 2016 Municipal Local Government Elections: implications for editorial policy - Muswede, T. (SAAPAM (South African Association of Public Administration and Management), 2016)
This paper evolves from the South African Broadcasting Corporation's decision to selectively broadcast images of protesters expressing decent over poor service delivery, particularly the destruction of public property towards the 2016 Local Government Municipal elections. It examines the editorial policy implications for such action against the public broadcaster's role to report news truthfully, accurately and objectively. As the sole provider of public broadcasting services in the country, the SABC is charged with the mandate to serve as a vehicle that carries the country's transformation agenda through contextualising national challenges, achievements and possibilities. This places high demands on the professional judgement of the editorial team to avoid being influenced by external pressure including that from political, commercial or other sectional interests in order to promote independent, transparent and non-partisan news coverage. However, following the new policy shift, the SABC was inundated with complaints as part of the national outcry that this action was tantamount to self-censorship and has the potential to trample on people's rights to freedom of expression, access to information and above all, their right to express unfettered dissent. Premised within the normative media theoretical framework, the paper argues that the editorial shift in news coverage has the potential to impede on the citizens' rights to exercise their "freedoms" in a democratic country. Furthermore, since the SABC is funded from the national fiscus, its editorial policy review initiatives must adhere to the standard code of practice, including holding consultative meetings with stakeholders. This will, among others, help the organisation to efficiently serve the populace to whom it is accountable as regulated in the broadcasting charter.
Article published in: SAAPAM Limpopo Chapter 5th Annual Conference Proceedings 2016
Keywords: Public broadcaster; Transparency; Editorial policy; Freedom of expression; Protests; Freedom of speech -- South Africa; Mass media -- South Africa; Censorship; Freedom of information